Den könsrelaterade diskrepansen i operasångares försörjningsmöjligheter - Bryngelsson,Mathilda (2023)
The first of my two purposes was to investigate whether there is a gender disparity in the possibilities to make a living as an opera singer. I collected empirical data on the number of jobs per fach and the gender breakdown of students at opera schools, and conducted a survey on how former students at Sweden's opera schools supported themselves. I concluded that there is a large disparity to the disadvantage of the female-associated fachs, since about two-thirds of jobs for opera soloists go to the singers of the male-associated fachs, and about two-thirds of trained singers belong to the female-associated fachs. As part of how to influence one’s own conditions by creating one’s own performances with a higher proportion of roles for the female-associated fachs, my second purpose was to explore the artistic challenges that arose as I adapted Massenet's Cendrillon (Cinderella) into a version in Swedish for family audiences. Five major challenges were discovered, all related to the work's dramaturgical, musical, or linguistic adaptation. These were resolved when I gave myself greater artistic freedom in the adaptation but adhered to the basic constraints of vocal technique, music theory, and dramaturgy.
Keywords: Opera; försörjning; könsdiskrepans; jämställdhet; kulturpolitik; barnopera; översättning; dramaturgi